La sospecha endémica argentina. La epidemia del miedo y la producción de (des)confianza en épocas de crisis sanitaria - Hortiguera, HUGO (Estudios sobre el Mensaje Periodístico, 2010)
Following the research by SILVERSTONE (2004) and VAN DIJK (1996, 1997, 1998, 2003), and taking as an excuse a very specific health problem, this paper aims to (1) analyzing how the contemporary Argentine media participate in the social space and interact with the political sphere, and (2) how they fight for the ownership and control of the public discourse and its meanings. Briefly, this study explores the understanding and extent of certain meanings spread by the media to build our uncertainties, and how these uncertainties become a marketable product and collaborate in the production of disbelief in our public institutions. The main textual corpus is a number of articles concerning the emergence and spread of the first symptoms of influenza A (H1N1) in Argentina, and published by three national newspapers (Clarín, La Nación and Página/12) between the 28th of April and 16th of July, 2009.
Keywords: Influenza A; Rumour; Sources; Fiction and veridiction; Credibility